Aplikasi Pengukuran Kinerja dengan Balanced Scorecard pada Rumah Sakit - Mesra Berlyn Hakim; Ali Djamhuri; Bambang Hariadi (Jurnal Riset dan Aplikasi: Akuntansi dan Manajemen, 2021)
This study analyze the Muhammadiyah Lamongan Hospital performance based on four perspectives: a financial, costumer, internal business, learning and growth. The research method used a case study. Research Results Measurement of the financial perspective shows that from the results of liquidity, profitability, and solvency, Muhammadiyah Hospital Lamongan gets good results. This study results from the perspective of customers that are generally also good, which is represented by the views of most customers who value hospital services as quite good.